«KiKli Fit» - The effects of a specifically designed physical activity program on cognitive and motor performance in children with cancer: A multicenter crossover trial - Ann Christin Schneider; Lisa Hillebrecht; Julia Schmid; Christina Schindera; Eva Katharina Brack; Valentin Benzing (Bern Open Publishing, 2024)
Introduction Children with cancer are at an increased risk for various physical and cognitive challenges due to their illness and its treatment. A concerning observation is that young cancer patients often lead sedentary or even lying lifestyles, clearly failing to meet the WHO's recommendation of 60 minutes of moderate-to-vigorous physical activity (PA) daily. This is alarming considering that PA is essential for physical and mental health, e.g., for the development of motor skills and cognitive functions (Bull et al., 2020). However, PA promotion in acute care in Swiss pediatric oncology units is hardly existent. Therefore, the aim of this project is to develop and conduct a physical activity program in a pediatric oncology unit and investigate its effects on cognitive and motor performance. Methods Part A of this project involved a qualitative study conducted at the Inselspital Bern's pediatric oncology unit, aiming to design a tailored PA therapy program. This part included patient interviews and staff surveys. Part B, which is ongoing, focuses on a forthcoming two-arm multicenter crossover-controlled trial. This trial will compare the exercise therapy and PA counseling (intervention group in Bern, n = 40) with standard treatment (control group in Basel, n = 40). Participants will be aged 6-18 years, newly diagnosed with cancer and undergoing cytotoxictreatment for at least six weeks. The 12-week program will consist of thrice-weekly, 45-minute sessions of individualized exercise, aligned with the SK2-guidelines, NAOK, and international Pediatric Oncology Exercise Guidelines (Götte et al., 2022; Wurz et al., 2021). The sessions will focus on motor skills and cognitively challenging PA. In addition, children will receive 4 exercise counseling sessions. To evaluate the study, there will be three measurement points (once at admission, after twelve weeks of intervention and one follow-up after six months). The outcome measures include motor and cognitive performance, physiological and psychosocial functioning. Results Initial findings from the qualitative study indicate a strong patient and staff interest in exercise therapy. The study also provided valuable insights for developing and implementing the intervention. Discussion/conclusion The results will reveal important insights relevant to research and practice. Adopting a research perspective, the results will shed light on the effects of PA on cognitive performance in acute cancer care. Adopting a more applied perspective, PA has been neglected in Swiss pediatric oncology units so far. Therefore, this study may contribute to proof the effectiveness of PA for childhood cancer patients and thus help implementing it in standard care in the long term. References Bull, F. C., Al-Ansari, S. S., Biddle, S., Borodulin, K., Buman, M. P., Cardon, G., Carty, C., Chaput, J.-P., Chastin, S., Chou, R., Dempsey, P. C., DiPietro, L., Ekelund, U., Firth, J., Friedenreich, C. M., Garcia, L., Gichu, M., Jago, R., Katzmarzyk, P. T., Lambert, E., Leitzmann, M., ... & Willumsen, J. F. (2020). World Health Organization 2020 guidelines on physical activity and sedentary behaviour. British Journal of Sports Medicine, 54(24), 1451-1462. https://doi.org/10.1136/bjsports-2020-102955 Götte, M., Gauß, G., Dirksen, U., Driever, P. H., Basu, O., Baumann, F. T., Wiskemann, J., Boos, J., & Kesting, S. V. (2022). Multidisciplinary Network ActiveOncoKids guidelines for providing movement and exercise in pediatric oncology: Consensus-based recommendations. Pediatric Blood & Cancer, 69(11), Article e29953. https://doi.org/10.1002/pbc.29953 Wurz, A., McLaughlin, E., Lategan, C., Chamorro Viña, C., Grimshaw, S. L., Hamari, L., Götte, M., Kesting, S., Rossi, F., van der Torre, P., Guilcher, G. M. T., McIntyre, K., & Culos-Reed, S. N. (2021). The international Pediatric Oncology Exercise Guidelines (iPOEG). Translational Behavioral Medicine, 11(10), 1915-1922. https://doi.org/10.1093/tbm/ibab028